2008
DOI: 10.1261/rna.1106408
|View full text |Cite
|
Sign up to set email alerts
|

Footprinting analysis demonstrates extensive similarity between eukaryotic RNase P and RNase MRP holoenzymes

Abstract: Eukaryotic ribonuclease (RNase) P and RNase MRP are evolutionary related RNA-based enzymes involved in metabolism of various RNA molecules, including tRNA and rRNA. In contrast to the closely related eubacterial RNase P, which is comprised of an RNA component and a single small protein, these enzymes contain multiple protein components. Here we report the results of footprinting studies performed on purified Saccharomyces cerevisiae RNase MRP and RNase P holoenzymes. The results identify regions of the RNA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 63 publications
14
64
1
Order By: Relevance
“…Others have suggested that this conserved GARAR element may form a pentaloop, P8 [38]. However, the P8 structure was not detected by holoenzyme footprinting analyses in vitro [39]. In our analysis, the P8 region was found to interact with proteins, suggesting that the conformation of P8 may change when it is bound by an RBP in vivo.…”
Section: Rbp Binding Facilitates Rna Secondary Structure Conformationcontrasting
confidence: 66%
“…Others have suggested that this conserved GARAR element may form a pentaloop, P8 [38]. However, the P8 structure was not detected by holoenzyme footprinting analyses in vitro [39]. In our analysis, the P8 region was found to interact with proteins, suggesting that the conformation of P8 may change when it is bound by an RBP in vivo.…”
Section: Rbp Binding Facilitates Rna Secondary Structure Conformationcontrasting
confidence: 66%
“…enzyme (Esakova et al 2008), which indicate that the eP15 loop is not involved in interactions with proteins, as are the results of mutational studies (Shadel et al 2000;Li et al 2004), which indicate that the terminal part of the eP15 stem is not essential for the function of RNase MRP.…”
Section: Resultsmentioning
confidence: 90%
“…We generated two yeast strains, each containing a TAP tag (Rigaut et al 1999) attached to the carboxyl terminus of RNase MRP/P protein component Pop4 Esakova et al 2008) plus a His 6 tag attached to the carboxyl terminus of either Pop5 or Rpp1. Active RNase MRP was purified from both yeast strains using established protocols Esakova et al 2008); the TAP tag was used as the purification handle. Following purification, RNase MRP was subjected to UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations